The Importance of Lambung Mangkurat Banjarbaru Archives And Museum In Towards Digital Archives - Dewicca Fatma Nadilla; Muhammad Rico (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
This research analyzes the importance of manuscript archives becoming digital the era information technology. Archives are important part historical research data, the transformation of archives from manuscripts to digital very necessary. This research uses historical methods with the steps of collecting the researched data, criticizing, interpreting and compiling historical events into stories. Obtain and validate research data, the researcher then conducted field research, namely interviews with museum managers, tour guides, and related agencies. The results the research illustrate that digitalization the most important thing in archive management. Changing the system from manuscript to digital archives can improve creativity, productivity, efficiency, and innovation performance. Digital archives manuscripts have become digital, providing convenience and easy access for every Museum visitor from any region. Other findings can be innovation for teachers teaching history school, thus giving the Lambung Mangkurat Museum distinction becoming more famous, example the Sangiran Museum in Central Java which digital.